Doing 'Dirt Research' in Northern Mining Towns: An Overview. (December 2022) - Keeling, Arn; Rodon, Thierry
Highlights: Fieldwork (broadly conceived) is central to the understanding of extractive industries and regions. Earlier generation of case- and field-based research could be faulted at times for a somewhat myopic focus on local encounters with extractive industries. In relation to extractive industries, there is a difficult balance between reflecting the intensely local and place-based factors and the insights gained through comparative analysis .